Optimal Incentive Mechanism for ISO 9001 Quality Audit: A Mechanism Design Approach - Jani Rahardjo; I Nyoman Sutapa; Togar Wiliater Soloan Panjaitan ((IJCSAM) International Journal of Computing Science and Applied Mathematics, 2026)
This paper develops a principal–agent model for ISO 9001:2015 quality audit in a manufacturing company, where the auditee is an informed agent and the auditor is a principal who designs an incentive-compatible audit mechanism. The proposed mechanism combines self-reported performance, risk-based audit probabilities, and quadratic penalties on deviations between reported and verified performance. We establish explicit mathematical conditions for incentive compatibility and individual rationality that guarantee truthful reporting and substantive compliance as the optimal strategy for the auditee. The mechanism is shown to be constrained Pareto optimal within a natural class of audit contracts: no alternative contract can increase the auditor’s expected utility without reducing the agent’s utility, given the informational constraints. We prove the uniqueness of this optimal solution given a maximum feasible penalty. A parametric sensitivity analysis and a case study from the Indonesian manufacturing sector illustrate how the choice of audit probability, certification benefit, and penalty parameter can transform a symbolic certification regime into an equilibrium with genuine quality improvement and credible ISO 9001 implementation